2016
DOI: 10.1038/npjpcrm.2016.68
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate use of inhaled corticosteroids in COPD: the candidates for safe withdrawal

Abstract: International guidance on chronic obstructive pulmonary disease (COPD) management recommends the use of inhaled corticosteroids (ICS) in those patients at increased likelihood of exacerbation. In spite of this guidance, ICS are prescribed in a large number of patients who are unlikely to benefit. Given the evidence of the risks associated with ICS and the limited indications for their use, there is interest in understanding the effects of withdrawing ICS when prescribed inappropriately. In this review, we disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Results from several studies have shown that long-term use of ICS alone or in combination with a LABA increased the risk of pneumonia. 11,[32][33][34] For example, in a 1-year double-blind study, the risk of pneumonia was significantly higher when an ICS was used in combination with a LABA versus LABA alone. 32 Further, findings from a patientlevel meta-analysis suggested that patients with COPD and lower blood eosinophil counts (<2%) who were treated with ICS had more pneumonia events than those with higher counts.…”
Section: Use Of Ics In Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from several studies have shown that long-term use of ICS alone or in combination with a LABA increased the risk of pneumonia. 11,[32][33][34] For example, in a 1-year double-blind study, the risk of pneumonia was significantly higher when an ICS was used in combination with a LABA versus LABA alone. 32 Further, findings from a patientlevel meta-analysis suggested that patients with COPD and lower blood eosinophil counts (<2%) who were treated with ICS had more pneumonia events than those with higher counts.…”
Section: Use Of Ics In Copdmentioning
confidence: 99%
“…55 Moreover, higher blood eosinophil counts are purported to predict increased exacerbation rates and greater treatment effect with LABA 1 ICS versus LABA alone in patients with COPD. 34,56,57 For example, in a post-hoc analysis of 2 clinical trials in patients with moderate-to-severe COPD and ≥1 exacerbation within a year before screening, the LABA 1 ICS combination of vilanterol 1 fluticasone furoate reduced exacerbations up to 24% in patients with blood eosinophil counts of ≥2 to <4%, 32% in those with counts of 4% to <6%, and 42% in those with counts ≥6% compared with vilanterol alone. 55 These results suggest that an increased blood eosinophil count is likely a predictive marker for response to ICS-based treatment in patients with COPD.…”
Section: Eosinophils As Markers Of Response To Icsmentioning
confidence: 99%
“…This manuscript is not aimed to discuss whether, when, why, and how ICS should or should not be prescribed in COPD [1][2][3] . Rather, our purpose is to examine the published literature to consider whether ICS can be safely discontinued in COPD patients who do not need them on the basis of the available evidence 4,5 . Interestingly, this is also on its way to become a classic debate 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that ICS are widely prescribed in patients with stable COPD regardless of any guidance recommendation, across all levels of airflow limitation severity and exacerbation risk [5][6][7][8][9][10][11][12] . It would be reasonable to state that ICS are overprescribed in COPD patients [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…The basis of this problem seems to lie in the chronic confusion between COPD and non-reversible or only partially reversible obstruction of the airways, that is, a functionally COPD. Moreover, safe withdrawal or deprescribing of ICS in patients with COPD should be done according to sound criteria [1].…”
mentioning
confidence: 99%